Supplementation of Mulberry (Morus indica) and Vernonia (V. amygdalina) leaves as protein source on morphometric measurement, weight change, and carcass characteristics of sheep - Gezahegn Mengistu; Getnet Assefa (CABI Agriculture and Bioscience)
Abstract Back ground Protein source supplement such as noug seed cake (NSC) has a greater cost. To overcome the problems associated with the shortage of protein source supplements, there is a need to look for options of protein source feeds preferably cheap, locally available, and easily accessible by farmers. In this regard, browse tree species such as mulberry (Morus indica) and Vernonia amygdalina represents a valuable option to overcome such problem. Methods We evaluated the feed intake, morphometric measurements, weight change, and carcass parameters of 25 male sheep, with initially weighed 20.8 ± 1.7 kg, supplemented for 90 days of experimental period. The treatments (diets) were the replacement of the protein in the NSC with iso-nitrogenous at (0, 25, 50, 75, and 100%) of mulberry and Vernonia mixed leaves meal. The sheep were given a basal diet of Rhodes grass hay, supplemented with 400.0 (D1), 429.8 (D2), 459.5 (D3), 489.3 (D4), and 519.0 (D5) g day− 1. The design was randomized complete block design (RCBD) with five animals in each treatment and replication. Results The total DM intake (g day− 1) was significantly higher in D3 (771.4) than in D1 (722.8) and D5 (642.8) but similar to D2 (754.9) and D4 (759.7). Chest-depth and hip-width were significantly influenced by the diets. The average daily gain of sheep in D1 (87.7), D2 (82.0), D3 (83.4), and D4 (75.2) were significantly higher than in D5 (56.0 g day− 1). The hot carcass weight of sheep fed D1 (14.1), D2 (13.7), D3 (12.7), and D4 (12.8) were significantly higher than sheep fed D5 (10.9 kg). Likewise, dressing percentage of sheep for D1 to D4 were higher than D5. Conclusion The results of the present investigation confirm that replacement of noug seed cake with mulberry and Vernonia mixed leaves meal up to 75% (25% NSC + 75% mulberry and Vernonia mixed leaves) achieved comparable result with concentrate mix in weight gain and carcass yield.